Implementation of the Drill Method in Arabic Language Learning for Grade VII Students at MTs Zia Salsabila Medan - Fadilah, Hikmatul; Taufiq, Muhammad (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This study aims to describe the implementation of the drill method in Arabic language learning for seventh-grade students at MTs Zia Salsabila Medan. The background of this research is based on the low level of active student participation in Arabic lessons and their weak vocabulary mastery, caused by a learning method that is less varied and tends to be monotonous. This study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The subjects of the study are the Arabic language teachers and seventh-grade students. The results show that the application of the drill method effectively increases student engagement and their retention of Arabic material. Students appeared more enthusiastic, gave positive responses, and showed significant improvement in pronunciation and understanding of sentence structure. Therefore, the drill method can be considered an effective alternative teaching strategy to improve Arabic learning outcomes, especially in the memorization of vocabulary at the junior high school level.